KAJIAN KESTABILAN INTI UNSUR-UNSUR PADA PROSES PELURUHAN ZAT RADIOAKTIF DENGAN PENDEKATAN ENERGI IKAT INTI MODEL TETES CAIRAN - Iko Mardiana; Trapsilo Prihandono; Yushardi Yushardi (FKIP Universitas Jember, 2019)
Abstract The purpose of this research is to calculate the binding energy and disintegration energy with the binding energy liquid drop model approach. This research is modeling research. The steps: 1) prepare supporting materials for research on stability and elements in the radioactive process; 2) reviewing materials that have been obtained previously; 3) do calculation simulation; 4) analyze and discuss the results of calculations; 5) conclude the results of the study. The calculation results show that the element has the largest binding energy of 1805,1 MeV and has the smallest binding energy per nucleon that is equal to 7,584 MeV, while the resulting child nuclide has the smallest binding energy of 1612,2747 MeV and has the largest binding energy per nucleon of 7,8266 MeV, so that the binding energy has a decreased graph while the binding energy per nucleon has a rising graph. The biggest disintegration energy in the uranium series decay process occurs at decay of alpha to be which is equal to 5,1037 MeV while the smallest disintegration energy occurs at beta decay becomes which is equal to -0,2639 MeV. Key word: Binding energy, disintegration energy,liquid drop model.